PENGARUH LITERASI KEUANGAN, EXPERIENCED REGRET, MOTIVASI DAN STATUS PENDIDIKAN TERHADAP KEPUTUSAN INVESTAI IRT - Dwi Lestari, Melita; Kusuma Wardani , Dewi (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2020)
Abstract This study aims to determine the effect of financial literacy, experienced regret, motivation, and educational status on investment decisions of housewives by taking a sample of the Community in Krembangan Village, Panjatan District, Kulon Progo Regency. The data used are primary data. The method used is multiple regression analysis. The sampling technique used in this study was snowball sampling and 100 data samples were obtained. Regression test results show that financial literacy has a positive effect on investment decisions of housewives, experienced regret has a negative effect on investment decisions of housewives, motivation does not affect investment decisions of housewives, educational status has a negative effect on investment decisions of housewives.